Harnessing Entrepreneurial Creativity and Green Opportunity Exploitability for Expansion Growth: Insights from the Real Estate Development Industry - Irawan Yuswono (Applied Business and Administration Journal, 2024)
This study explores the pivotal role of entrepreneurial creativity in driving business opportunity exploitability and its subsequent impact on firm performance within the environmentally friendly housing development industry in Indonesia. Employingthe Resource-Based View (RBV) theory, the research investigates the relationship between entrepreneurial creativity and business expansion through green innovation approaches. Data were collected via surveys and interviews with 188 housing developers and contractors in major Indonesian cities, revealing that firms integrating entrepreneurial creativity with green innovations are more likely to expand successfully. The findings highlight the necessity of unique and inimitable resources, such as green innovation and entrepreneurial creativity, for achieving competitive advantages and superior firm performance. The study underscores the importance of strategic resource utilization in sustainable development and provides actionable insights for housing developers and policymakers to foster innovation and sustainability in the real estate sector. These insights contribute to the broader literature on sustainable entrepreneurship and offer a strategic framework for leveraging green business opportunities to enhance firm performance.